Understanding lipidomics associations and the lipoprotein-related caveats in population epidemiology - Zhao, Siyu; Ohukainen, Pauli; Kettunen, Johannes; Järvelin, Marjo-Riitta; Kähönen, Mika; Lehtimäki, Terho; Viikari, Jorma; Raitakari, Olli T; Mäkinen, Ville-Petteri; Ala-Korpela, Mika (Oxford University Press, 2025)
Mass spectrometry lipidomics is becoming customary to analyse serum/plasma samples in epidemiology. The measurables are molecular constituents of lipoprotein particles, but very little is known on the consequences of adjusting lipidomics data with lipoprotein measures. We studied two population cohorts with 5,657 and 2,036 participants. LC-MS/MS lipidomics was applied to analyse 24 molecular lipid classes and NMR spectroscopy to quantify seven lipoprotein lipids plus apolipoprotein A-I (apoA-I) and B (apoB). The associations of these measures were analysed via partial Spearman's correlations. The effects of nine different lipoprotein adjustments on these interrelationships were assessed. Multivariable regression modelling with these adjustments was also performed for the associations between the lipidomics data and BMI. These novel large-scale lipidomics data and their associations between the lipoprotein measures were coherent in both population cohorts, confirming the compatibility of the analytical approaches. Simulated data were generated to corroborate the mediation effects. The lipoprotein-related lipid-transport and metabolism inherently mediate the lipidomics associations as evident from the striking effects of the lipoprotein adjustments. These effects and their relevance to the interpretations of lipidomics data are presented and discussed in detail for the first time. The combined lipoprotein lipid adjustments appear prone to overadjustment and arbitrary biases.